2016
DOI: 10.18097/pbmc20166204391
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic modification of low-density lipoproteins

Abstract: 2 Российский экономический университет им. Г.В. Плеханова, 117997, Москва, Стремянный переулок, 36 3 НИИ атеросклероза (Сколково), а/я №21, 121609, Москва Одним из наиболее ранних проявлений атеросклероза является вне-и внутриклеточное отложение липидов, преимущественно эфиров холестерина, в артериальной интиме. В крови человека были обнаружены модифицированные липопротеины низкой плотности (ЛНП), которые, как предполагается, и вызывают накопление липидов в артериальной стенке, то есть являются атерогенными. В… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Desialylated LDL particles were also shown to contain less antioxidants and dwell for a longer time in the subendothelial space of the arterial wall, which may explain their increased susceptibility to oxidation. As a result, atherogenic multiple-modified LDL is generated in atherosclerosis-prone individuals [18,19]. Oxidized LDL accumulates in predisposed for atherosclerosis areas of the arterial wall and contributes to the increased expression of vascular cell adhesion molecules-1 (VCAM-1), P, and E-selectins and other cell adhesion molecules on the endothelial cells.…”
Section: Oxidative Stress In Atherosclerosismentioning
confidence: 99%
“…Desialylated LDL particles were also shown to contain less antioxidants and dwell for a longer time in the subendothelial space of the arterial wall, which may explain their increased susceptibility to oxidation. As a result, atherogenic multiple-modified LDL is generated in atherosclerosis-prone individuals [18,19]. Oxidized LDL accumulates in predisposed for atherosclerosis areas of the arterial wall and contributes to the increased expression of vascular cell adhesion molecules-1 (VCAM-1), P, and E-selectins and other cell adhesion molecules on the endothelial cells.…”
Section: Oxidative Stress In Atherosclerosismentioning
confidence: 99%
“…Subendothelial lipid accumulation plays a crucial role in the development of atherosclerotic lesions in the arterial cells. The extra- and intracellular lipid deposition predominantly of cholesterol esters leading to the formation of foam cells in the arterial intima is not only one of the earliest manifestations of atherosclerosis (preclinical atherogenesis) but also the triggering event of the onset of atherosclerotic lesion development [19]. The cells populating atherosclerotic lesions are called foam cells for the foamy appearance of their cytoplasm, which is almost completely loaded with lipid inclusions [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in the blood of most patients with coronary atherosclerosis there are circulating IC, consisting of LDL and anti-LDL antibodies [22] . An increase in the level of m-LDL and a high titer of antibodies to them in patients with diabetes with an existing cardiovascular pathology was revealed in comparison with the control group [23] .…”
Section: Multiple Modification Of Ldl In Blood Plasmamentioning
confidence: 85%